Follicular fluid-derived exosomal HMOX1 promotes granulosa cell ferroptosis involved in follicular atresia in geese (Anser cygnoides) - Yu Zhang; Youluan Jiang; Xiaoqian Dong; Shuwen Luo; Guoyu Jiao; Kaiqi Weng; Qiang Bao; Yang Zhang; Wanwipa Vongsangnak; Guohong Chen; Qi Xu (Poultry Science, 2024)
ABSTRACT: The proliferation and death of granulosa cells (GCs) in poultry play a decisive role in follicular fate and egg production. The follicular fluid (FF) contains a variety of nutrients and genetic substances to ensure the communication between follicular cells. Exosomes, as a new intercellular communication, could carry and transport the proteins, RNA, and lipids to react on GCs, which had been found in FF of various domestic animals. Whether exosomes of FF in poultry play a similar role is unclear. In this study, geese, a poultry with low egg production, were chosen, and the effect of FF exosomes on the proliferation and death of GCs was investigated. Firstly, there were not only a large number of healthy small yellow follicles (HSYFs) but also some atresia small yellow follicles (ASYFs) in the egg-laying stage. Also, the GC layers of ASYFs became loose interconnections, inward detachment, and diminished survival rate than that of HSYFs. Besides, compared to HSYFs, the contents of E2, P4, and the mRNA expression levels of ferroptosis-related genes GPX4, FPN1, and FTH1 were significantly decreased, while COX2, NCOA4, VDAC3 mRNA were significantly increased, and the structure of mitochondrial cristae disappeared and the outer membrane broke in the GC layers of ASYFs. Moreover, the ROS, MDA, and oxidation levels in the GC layers of ASYFs were significantly higher than those of HSYFs. All these hinted that ferroptosis might result in a large number of GCs death and involvement in follicle atresia. Secondly, FF exosomes were isolated from HSYFs and ASYFs, respectively, and identified by TEM, NTA, and detection of exosome marker proteins. Also, we found the exosomes were phagocytic by GCs by tracking CM‐Dil. Moreover, the addition of ASYF-FF exosomes significantly elevated the MDA content, Fe2+ levels, and the mitochondrial membrane potential (MMP) in GCs, thus significantly inhibiting the proliferation of GCs, which was restored by the ferroptosis inhibitor ferrostatin-1. Thirdly, the proteomic sequencing was performed between FF-derived exosomes of HSYFs and ASYFs. We obtained 1615 differentially expressed proteins, which were mainly enriched in the protein transport and ferroptosis pathways. Among them, HMOX1 was enriched in the ferroptosis pathway based on differential protein-protein interaction network analysis. Finally, the role of HMOX1 in regulating ferroptosis in GCs was further explored. The highly expressed HMOX1 was observed in the exosomes of ASYF-FF than that in HSYF-FF. Overexpression of HMOX1 increased ATG5, LC3II, and NCOA4 expression and reduced the expression of FTH1, GPX4, PCBP2, FPN1 in the ferroptosis pathway, also promoted intracellular Fe2+ accumulation and MDA surge, which drove ferroptosis in GCs. The effects of HMOX1 on ferroptosis could be blocked by its inhibitor Znpp. Taken together, the important protein HMOX1 was identified in FF, which could be delivered to GCs via exosomes, triggering ferroptosis and thus determining the fate of follicles.